PADI4 genotype is not associated with rheumatoid arthritis in a large UK Caucasian population. Issue 4 (25th May 2009) - Burr, Marian L; Naseem, Haris; Hinks, Anne; Eyre, Steve; Gibbons, Laura J; Bowes, John; Wilson, Anthony G; Maxwell, James; Morgan, Ann W; Emery, Paul; Steer, Sophia; Hocking, Lynne; et al.
Abstract : Background: Polymorphisms of the peptidylarginine deiminase type 4 ( PADI4 ) gene confer susceptibility to rheumatoid arthritis (RA) in East Asian people. However, studies in European populations have produced conflicting results. This study explored the association of the PADI4 genotype with RA in a large UK Caucasian population. Methods: The PADI4_94 (rs2240340) single nucleotide polymorphism (SNP) was directly genotyped in a cohort of unrelated UK Caucasian patients with RA (n=3732) and population controls (n=3039). Imputed data from the Wellcome Trust Case Control Consortium (WTCCC) was used to investigate the association of PADI4_94 with RA in an independent group of RA cases (n=1859) and controls (n=10 599). A further 56 SNPs spanning the PADI4 gene were investigated for association with RA using data from the WTCCC study. Results: The PADI4_94 genotype was not associated with RA in either the present cohort or the WTCCC cohort. Combined analysis of all the cases of RA (n=5591) and controls (n=13 638) gave an overall OR of 1.01 (95% CI 0.96 to 1.05, p=0.72). No association with anti-CCP antibodies and no interaction with either shared epitope or PTPN22 was detected. No evidence for association with RA was identified for any of the PADI4 SNPs investigated. Meta-analysis of previously published studies and our data confirmed no significant association between the PADI4_94 genotype and RA in people of European descent (OR 1.06, 95% CI 0.99 to 1.13, p=0.12). Conclusion: In the largest study performed to date, the PADI4 genotype was not a significant risk factor for RA in people of European ancestry, in contrast to Asian populations.